2005
DOI: 10.1200/jco.2005.06.117
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Adaptive Outcome in Low-Grade Pediatric Cerebellar Astrocytomas: Evidence of Diminished Cognitive and Adaptive Functioning in National Collaborative Research Studies (CCG 9891/POG 9130)

Abstract: We did not replicate previous findings of location-specific effects on cognitive or adaptive outcome. However, the elevated risk of deficits in this population runs contrary to clinical lore, and suggests that clinicians should attend to the functional outcomes of children who undergo only surgical treatment for cerebellar tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 25 publications
8
155
1
2
Order By: Relevance
“…We thus join a number of studies equally failing to find such an effect. 2,15,17 However, the mean age of our patient sample at the time of diagnosis was 8 years and the youngest patient was 3.7 years old at the time of surgery. This circumstance does not allow for far-fetched conclusions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We thus join a number of studies equally failing to find such an effect. 2,15,17 However, the mean age of our patient sample at the time of diagnosis was 8 years and the youngest patient was 3.7 years old at the time of surgery. This circumstance does not allow for far-fetched conclusions.…”
Section: Discussionmentioning
confidence: 82%
“…1 At the same time, there is a strong notion in the corresponding literature that CPA patients fare very well and that their overall outcome regarding education, QoL, and cognitive functioning is favorable (see refs. 2,1922 ). Zuzak and colleagues 22 for instance found that CPA patients rated their health-related quality of life (HRQoL) similarly or even higher than a group of healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented lower or suboptimal intellectual and adaptive outcomes in pediatric brain tumor survivors compared to their healthy peers (Beebe et al, 2005;Papazoglou, King, Morris, & Krawiecki, 2008). Longitudinal studies have reported that these children are acquiring intellectual and adaptive skills at a slower rate relative to their same age peers but are not losing skills over time (Netson, Conklin, Wu, Xiong, & Merchant, 2013;Palmer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining short term survivorship (2 years or less post treatment) suggest decoding vulnerability in children treated with radiation therapy and also in those treated with surgery only (Beebe, et al, 2005;Reeves, et al, 2006). Furthermore, longitudinal data indicate slower reading skill development in survivors over time, with decoding scores on average remaining below normative scores, signifying that survivors have more delays in the rate at which they are developing reading skills (Mabbott, et al, 2008;Mulhern et al, 2005;Reddick, et al, 2003). A more recent study observed slower learning of reading decoding skills in survivors (Conklin, Li, Xiong, Ogg, & Merchant, 2008), and also found that while standard scores for reading declined over time (median follow up time of 60 months), scores for spelling and math achievement remained at par with peers.…”
Section: Model Of Reading In Brain Tumor Survivorsmentioning
confidence: 99%
“…In survivors, academic achievement is considered a distal marker of a set of underlying deficits in core cognitive skills such as processing speed, attention, and memory (Mabbott et al, 2005;Mulhern, et al, 2005;Palmer, 2008). In Palmer's (2008) developmental cascade model of the neurodevelopmental impacts of brain tumors, disease and treatment risk factors were proposed to be associated with broad outcomes of academic achievement and intelligence.…”
Section: Model Of Reading In Brain Tumor Survivorsmentioning
confidence: 99%